UJI PENGGUNAAN FORMULASI TRICHOKOMPOS TKKS DENGAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) ASAL KECAMBAH KEMBAR - Roberi Sinaga; Sampoerno '; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objectives of this research are to find out the influence of trichokompos TKKS with NPK fertilizer formulations and to get the best treatment of formulation for the growth of oil palm seedling (Elaeis guineensis Jacq.)which derived of multy embrio. This research has been conducted in the Agriculture Experimental Station Faculty of Agriculture, University of Riau, District of Tampan, the research was carried out for 4 months starting in September 2014 to Desember 2014. This research arranged experimentally using Completely Randomized Design (CRD), consist of 5 treatments and 3 replications, so obtained 15 units of experiment. The treatments are P0:Without fertilizer,P1: Trichokompos TKKS 74,5 g/polybag+ NPK 2 tablet. P2: Trichokompos TKKS 74,5 g/polybag+ NPK 4 tablet.P3:Trichokompos TKKS 124,5 g/polybeg + NPK 2 tablet. P4:Trichokompos 124,5 g/polybag + NPK 4 tablet. Analysis of variance result showing significantly difference, continued with Duncans New Multiple Range Test (DNMRT)at level 5%. Based on research result which has been done indicates that giving various doses of trichokompos TKKS with NPK fertilizer formulations give an significantly effect on all parameters observed. From this research giving the best formulation at dose 124,5 g trichokompos TKKS + 4 Tablet NPK on all parameter observed.The final results of observationsshowing that the average of high, number of leaves and cusps diameter oil palm seedlingof multy embrio origin which aged 6 months has exceeded the growth standards issued by PPKS.So oil palm seedling of multy embrio origin worth for use as plant material. Keywords:Oil palm, Multy embrio, Trichokompos TKKS, NPK fertilizer.